PERAN KEPUASAN KERJA TERHADAP PENINGKATAN KINERJA KARYAWAN YANG DIMEDIASI OLEH PRODUKTIVITAS KARYAWAN PADA PT.ORISA UTAMA SEJAHTERA CIPOCOK JAYA SERANG - Rustia, Eneng; Hidayat, Syamsul; Suflani, Suflani (National Conference on Applied Business, Education, & Technology (NCABET), 2024)
Changes from within the organizational environment and from outside the organization. 1. To find out whether Job Satisfaction has an effect on employee productivity at PT. Orisa Utama Sejahtera. 2. To find out whether job satisfaction affects the performance of PT. Orisa Utama Sejahtera employees. 3. To find out whether productivity affects the performance of PT employees. Orisa Utama Sejahtera. 4. To find out whether job satisfaction affects employee performance through productivity at PT. Orisa Utama Sejahtera.   In this research, researchers used quantitative research methods. The conclusion of this research is that there is an influence of job satisfaction on employee productivity, there is an influence of job satisfaction on employee productivity, there is no influence of productivity on employee performance, there is no influence of job satisfaction on employee performance through employee productivity